A Phenomenological Critique of Darwin's Theory of Human Origins and Its Cultural Implications - Iskandarsyah Siregar (Lakhomi Journal Scientific Journal of Culture, 2024)
This article critically examines Darwin's theory of human origins through a phenomenological lens, highlighting perceived misconceptions embedded within the narrative of evolution. While Darwin's theory, emphasizing natural selection and biological processes, has profoundly influenced scientific thought, it has also faced significant scrutiny for its reductionist approach to human existence. This study explores how the theory often overlooks humanity's spiritual, cultural, and moral dimensions, reducing humans to mere biological entities. By analyzing phenomenological critiques and participant narratives, the article reveals the limitations of Darwinian evolution in fully explaining human consciousness, identity, and purpose. It also discusses the cultural and ethical implications of applying Darwinian principles to society, particularly concerning social inequality and moral relativism. The study concludes by advocating for integrative frameworks that combine scientific understanding with humanistic values, encouraging interdisciplinary dialogue and alternative perspectives on human origins.